CHARACTERIZATION OF TORREFIED EMPTY FRUIT BUNCH AND PALM KERNEL SHELL IN THE PRESENCE OF BIOMASS PELLET COMBUSTION GAS - SELLAPPAH, VARSHETA (2020)
Being the world second largest producer and exporter of palm oil, Malaysia’s palm oil industry generate a total of 85 – 110 million tonnes of solid biomass annually and a large percentage of these biomass are left underutilized due to its inferior properties compared to commercial solid fuels. Torrefaction, a mild thermochemical pre-treatment at 473 – 573K in inert atmosphere is proven as one of the promising methods in producing an energy denser biomass. However, continuous supply of nitrogen gas for torrefaction is a challenge in commercializing this technology for a large-scale biofuel production. In view of this, industrial flue gas has been proposed as a torrefaction gas to replace nitrogen gas.